PCR-RFLP ANALYSIS OF THE 16S RRNA AND ITS REGIONS IN BACTERIAL BLIGHT (XANTHOMONAS AXONOPODIS PV. PUNICAE) ACROSS POMEGRANATE FARMS IN KURDISTAN REGIONS-IRAQ. - Dalal Y. Kh. Sinjare; Jaladet M. S. Jubrael (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
Bacterial blight caused by Xanthomonas axonopodis pv. punicae (Xap) is a major biotic diseases in pomegranate (Punica granatum L.). In the field survey which lasted 2 year in six different geographical locations, Xap strains from the severely infected plant material collected including DuhokCcenter, around Erbil, Zaxo, south of Duhok, Akre, and Amedi. Xanthomonas was detected from infected plant material and its identity was confirmed by morphological, Microbial and Molecular Characterization. To study its genetic variability and phylogenetic relationship two important loci were targeted namely ITS region of 16s rDNA, 16S rRNA and then a PCR-RFLP was performed for PCR product of 16s rRNA loci using Hinf I, Hae III, and Rsa I restriction enzymes. The PCR-RFLP showed the genetic similarity coefficient ranging from 1.00 to 3.73, and the dendrogram grouped all tested strains in 4 clusters. The result revealed that this disease is in blooming stage in the country which was thought that has not been recorded before in pomegranate. To the best of our knowledge this is the first record of Xap. In Kurdistan/ Iraq therefore, further studies are needed to be performed to manage this hazardous bacterium.